Amniotic-Umbilical-to-Cerebral Ratio-A Novel Ratio Combining Doppler Parameters and Amniotic Fluid Volume to Predict Adverse Perinatal Outcome in SGA Fetuses at Term - Stumpfe, Florian; Faschingbauer, Florian; Kehl, Sven; Pretscher, Jutta; Emons, Julius; Gaß, Paul; Mayr, Andreas; Schmid, Matthias; Beckmann, Matthias; Stelzl, Patrick (Ultraschall in der Medizin, 2020)
Purpose â Introduction of a novel ratio-the amniotic-umbilical-to-cerebral ratio (AUCR)-to predict adverse perinatal outcome in SGA fetuses at term and comparison of its predictive accuracy with established parameters. Materials and Methods â This retrospective cohort study included 165 singleton pregnancies with SGA fetuses (birth weight <âŠ10 thpercentile) at term. Cases with planned vaginal delivery and documented pulsatility indices (PI) of the umbilical artery (UA), middle cerebral artery (MCA), and single deepest pocket (SDP) were included. CPR was calculated as the ratio between MCA PI and UA PI, UCR as the ratio between UA PI and MCA PI. AUCR was defined as follows: SDP/(UA PI/MCA PI). Adverse perinatal outcomes were defined as operative intervention (OI), OI due to fetal distress, admission to the neonatal intensive care unit (NICU), and composite adverse perinatal outcome (CAPO). Associations between Doppler parameters and these outcomes were estimated using regression analyses. Results â OI was statistically significantly associated with UCR, SDP, and AUCR, whereas no association was observed for UA PI, MCA PI, and CPR. Fetuses requiring OI due to fetal distress revealed a significantly higher UA PI and UCR as well as a lower MCA PI, CPR, and AUCR. With regard to NICU admission and CAPO, a significantly higher UA PI and lower CPR were found. Furthermore, a significant association was shown for SDP, UCR, and AUCR. AUCR achieved the best area under the curve for all outcome parameters. Conclusion â AUCR leads to an improvement in the prediction of unfavorable outcome in SGA fetuses at term. Furthermore, results of our study show that UCR might be superior to CPR.
CRIS-Team Scopus Importer:2020-11-13
Keywords: amniotic fluid; AUCR; CPR; SDP; UCR

Cerebroplacental versus Umbilicocerebral Ratio—Analyzing the Predictive Value Regarding Adverse Perinatal Outcomes in Low- and High-Risk Fetuses at Term - Stumpfe, Florian; Mayr, Andreas; Schneider, Michael; Kehl, Sven; Stübs, Frederik; Antoniadis, Sophia; Titzmann, Adriana; Pontones, Constanza; Bayer, Christian M.; Beckmann, Matthias; Faschingbauer, Florian (Medicina, 2023)
Background and Objectives: The aim of this study was to investigate the prediction of adverse perinatal outcomes using the cerebroplacental (CPR) and umbilicocerebral (UCR) ratios in different cohorts of singleton pregnancies. Materials and Methods: In this retrospective cohort study, we established our own Multiple of Median (MoM) for CPR and UCR. The predictive value for both ratios was studied in the following outcome parameters: emergency cesarean delivery, operative intervention (OI), OI due to fetal distress, 5-min Apgar < 7, admission to neonatal intensive care unit, and composite adverse perinatal outcome. The performance of the ratios was assessed in the following cohorts: total cohort (delivery ≥ 37 + 0 weeks gestation, all birth weight centiles), low-risk cohort (delivery ≥ 37 + 0 weeks gestation, birth weight ≥ 10. centile), prolonged pregnancy cohort (delivery ≥ 41 + 0 weeks gestation, birth weight ≥ 10. centile) and small-for-gestational-age fetuses (delivery ≥ 37 + 0 weeks gestation, birth weight < 10. centile). The underlying reference values for MoM were estimated using quantile regression depending on gestational age. Prediction performance was evaluated using logistic regression models assessing the corresponding Brier score, combining discriminatory power and calibration. Results: Overall, 3326 cases were included. Across all cohorts, in the case of a significant association between a studied outcome parameter and CPR, there was an association with UCR, respectively. The Brier score showed only minimal differences for both ratios. Conclusions: Our study provides further evidence regarding predictive values of CPR and UCR. The results of our study suggest that reversal of CPR to UCR does not improve the prediction of adverse perinatal outcomes.
CRIS-Team Scopus Importer:2023-09-08
Keywords: cerebroplacental ratio; CPR; UCR; umbilicocerebral ratio

Gestational diabetes mellitus and COVID-19: results from the COVID-19–Related Obstetric and Neonatal Outcome Study (CRONOS) - Kleinwechter, Helmut J.; Weber, Katharina S.; Mingers, Nina; Ramsauer, Babett; Schaefer-Graf, Ute M.; Groten, Tanja; Kuschel, Bettina; Backes, Clara; Banz-Jansen, Constanze; Berghaeuser, Martin A.; Brotsack, Irene A.; Dressler-Steinbach, Iris; et al. (American Journal of Obstetrics and Gynecology, 2022)
Background: Gestational diabetes mellitus is one of the most frequent pregnancy complications with a global prevalence of 13.4% in 2021. Pregnant women with COVID-19 and gestational diabetes mellitus are 3.3 times more likely to be admitted to an intensive care unit than women without gestational diabetes mellitus. Data on the association of gestational diabetes mellitus with maternal and neonatal pregnancy outcomes in pregnant women with SARS-CoV-2 infection are lacking. Objective: This study aimed to investigate whether gestational diabetes mellitus is an independent risk factor for adverse maternal and fetal and neonatal outcomes in pregnant women with COVID-19. Study Design: The COVID-19-Related Obstetric and Neonatal Outcome Study is a registry-based multicentric prospective observational study from Germany and Linz, Austria. Pregnant women with clinically confirmed COVID-19 were enrolled between April 3, 2020, and August 24, 2021, at any stage of pregnancy. Obstetricians and neonatologists of 115 hospitals actively provided data to the COVID-19-Related Obstetric and Neonatal Outcome Study. For collecting data, a cloud-based electronic data platform was developed. Women and neonates were observed until hospital discharge. Information on demographic characteristics, comorbidities, medical history, COVID-19–associated symptoms and treatments, pregnancy, and birth outcomes were entered by the local sites. Information on the periconceptional body mass index was collected. A primary combined maternal endpoint was defined as (1) admission to an intensive care unit (including maternal mortality), (2) viral pneumonia, and/or (3) oxygen supplementation. A primary combined fetal and neonatal endpoint was defined as (1) stillbirth at ≥24 0/7 weeks of gestation, (2) neonatal death ≤7 days after delivery, and/or (3) transfer to a neonatal intensive care unit. Multivariable logistic regression analysis was performed to evaluate the modulating effect of gestational diabetes mellitus on the defined endpoints. Results: Of the 1490 women with COVID-19 (mean age, 31.0±5.2 years; 40.7% nulliparous), 140 (9.4%) were diagnosed with gestational diabetes mellitus; of these, 42.9% were treated with insulin. Overall, gestational diabetes mellitus was not associated with an adverse maternal outcome (odds ratio, 1.50; 95% confidence interval, 0.88–2.57). However, in women who were overweight or obese, gestational diabetes mellitus was independently associated with the primary maternal outcome (adjusted odds ratio, 2.69; 95% confidence interval, 1.43–5.07). Women who were overweight or obese with gestational diabetes mellitus requiring insulin treatment were found to have an increased risk of a severe course of COVID-19 (adjusted odds ratio, 3.05; 95% confidence interval, 1.38–6.73). Adverse maternal outcomes were more common when COVID-19 was diagnosed with or shortly after gestational diabetes mellitus diagnosis than COVID-19 diagnosis before gestational diabetes mellitus diagnosis (19.6% vs 5.6%; P<.05). Maternal gestational diabetes mellitus and maternal preconception body mass index of ≥25 kg/m2 increased the risk of adverse fetal and neonatal outcomes (adjusted odds ratio, 1.83; 95% confidence interval, 1.05–3.18). Furthermore, overweight and obesity (irrespective of gestational diabetes mellitus status) were influential factors for the maternal (adjusted odds ratio, 1.87; 95% confidence interval, 1.26–2.75) and neonatal (adjusted odds ratio, 1.81; 95% confidence interval, 1.32–2.48) primary endpoints compared with underweight or normal weight. Conclusion: Gestational diabetes mellitus, combined with periconceptional overweight or obesity, was independently associated with a severe maternal course of COVID-19, especially when the mother required insulin and COVID-19 was diagnosed with or after gestational diabetes mellitus diagnosis. These combined factors exhibited a moderate effect on neonatal outcomes. Women with gestational diabetes mellitus and a body mass index of ≥25 kg/m2 were a particularly vulnerable group in the case of COVID-19.
CRIS-Team Scopus Importer:2022-09-02
Keywords: diabetes mellitus; invasive ventilation; large for gestational age; maternal pregnancy outcomes; morbidity; obesity; pregnancy; SARS-CoV-2

Influence of Preeclampsia on Induction of Labor at Term: A Cohort Study - Pretscher, Jutta; Weiss, Christel; Dammer, Ulf; Stumpfe, Florian; Faschingbauer, Florian; Beckmann, Matthias; Kehl, Sven (In Vivo, 2020)
Background/Aim: Even though vaginal delivery is a feasible option in patients with preeclampsia, the cesarean section rate in those patients is high. The aim of this study was to evaluate the influence of preeclampsia on induction of labor at term. Patients and Methods: This historical cohort study analyzed inductions of labor in women at term having preeclampsia versus women who were induced due to other reasons. The primary outcome measure was the cesarean section rate. Results: The cesarean section rate was higher in the preeclampsia group for both nulliparous and multiparous women after induction of labor but failed to reach statistical significane. The induction-to-delivery interval was longer in nulliparous women and the rate of vaginal birth within 48 h was lower in the nulliparous patiens with preeclampsia. However, the impact of preeclampsia on the cesarean section rate was not significant in the multivariable analysis following adjustment for BMI and parity. Conclusion: Preeclampsia at term did not influence the cesarean section rate in nulliparous and parous women when labor was induced.
CRIS-Team WoS Importer:2020-05-22

Influence of Sonographic Fetal Weight Estimation Inaccuracies in Macrosomia on Perinatal Outcome - Pretscher, Jutta; Kehl, Sven; Stelzl, Patrick; Stumpfe, Florian; Mayr, Andreas; Schmid, Matthias; Staerk, Christian; Schild, Ralf; Beckmann, Matthias; Faschingbauer, Florian (Ultraschall in der Medizin, 2020)
Objective To evaluate the influence of inaccurate sonographic fetal weight estimation in macrosomia on the mode of delivery and neonatal outcome (NO). Methods In 14633 pregnancies between 2002 and 2016, this retrospective study evaluated the association between sonographic fetal weight estimation, true birth weight (BW), mode of delivery (primary cesarean section [pCS], secondary cesarean section, vaginal delivery, and operative vaginal delivery rates) and NO parameters (5-min Apgar <7, pH <7.1, neonatal intensive care unit [NICU] admission, shoulder dystocia). Singleton pregnancies >37+0 weeks with ultrasound-estimated fetal weight (EFW) within 7 days before delivery were included. The study population was divided into four groups: Group 1 (false-negative): EFW <4000g/BW ≥4000g; Group 2 (true-positive): EFW ≥4000g/BW ≥4000g; Group 3 (false-positive): EFW ≥4000g/BW <4000g; and Group 4 (true-negative): EFW <4000g/BW <4000g. Results As expected, the highest secondary cesarean section (sCS) rate was found in Group 2 (true-positive) (30.62%), compared with only 17.68% in Group 4 (true-negative). The sCS rate in the false-positive Group 3 was significantly higher (28.48%) in comparison with the false-negative Group 1 (21.22%; OR 1.48; 95% CI, 1.16 to 1.89; P=0.002). In comparison with the true-negative Group 4, univariate analyses showed significantly higher rates for sCS in all other groups: Odds ratio (OR) 2.06 for Group 2 (95% CI, 1.74 to 2.42; P<0.001), 1.85 for Group 3 (95% CI, 1.54 to 2.22, P <0.001), and 1.25 for Group 1 (95% CI, 1.05 to 1.49; P <0.01). No significant differences were found for NO between Groups 1 and 3 for the parameters 5-min Apgar <7 (P=0.75), pH <7.1 (P=0.28), or NICU admission (P=0.54). However, there was a significantly higher chance for shoulder dystocia in Group 1 compared with Group 3 (OR 4.58; 95% CI, 1.34 to 24.30; P=0.008). Conclusion Sonographic EFW inaccuracies in fetal macrosomia appear to have a greater impact on the mode of delivery than birth weight itself. Underestimation of fetal weight may be associated with a higher probability of shoulder dystocia.
CRIS-Team Scopus Importer:2021-04-19
Keywords: cesarean section rate; fetal macrosomia; fetal weight estimation; perinatal outcome; sonography

Influence of sonographic fetal weight estimation in (suspected) fetal macrosomia on perinatal outcome - Pretscher, Jutta; Kehl, Sven; Stelzl, Patrick; Stumpfe, Florian; Mayr, A.; Schmid, M.; Staerk, C.; Schild, R. L.; Beckmann, Matthias; Faschingbauer, Florian (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Influence of Timing of Antenatal Corticosteroid Administration on Morbidity of Preterm Neonates - Morhart, Patrick; Gärtner, Janis; Weiss, Christel; Stumpfe, Florian; Dammer, Ulf; Faschingbauer, Florian; Fahlbusch, Fabian; Beckmann, Matthias; Kehl, Sven (In Vivo, 2022)
Background/Aim: We investigated the impact of the timing of antenatal corticosteroid (ACS) administration on the clinical outcome of preterm infants. Patients and Methods: Two hundred and fifty-five preterm infants between 28+0 and 34+0 weeks of gestation were retrospectively assigned to one of two groups: In the first group, ACS was given within 7 days before birth; the second group, did not receive ACS during that period. The primary outcome parameter was respiratory failure (defined by need for continuous positive airway pressure or mechanical ventilation) due to grade 1-4 respiratory distress syndrome (RDS). Secondary outcomes included the rates of intraventricular hemorrhage (IVH), periventricular leukomalacia, and necrotizing enterocolitis. Results: The rate of RDS was significantly higher in the no ACS group (40% vs. 62%, p=0.0009), especially of the more severe grades 24 (n=37 vs. n=48, p=0.0121). In addition, IVH (1% vs. 9%, p=0.0041) and neonatal infections (72% vs. 89%, p=0.0025) were significantly increased. Univariable and multivariable regression analyses showed a lower likelihood of RDS in the ACS group [odds ratio (OR)=0.295] in infants born closer to term (OR=0.907) and following preterm onset of labor (OR=0.495). Similarly, we observed a lower probability of IVH in the ACS group (OR=0.098), with a higher probability of occurrence of IVH in pre-eclampsia/HELLP syndrome (hemolysis, elevated liver enzyme levels, low platelet count) (OR=7.914). Conclusion: ACS treatment within the last 7 days before birth significantly reduced the risk of RDS and IVH in preterm. These data emphasize that the timing of ACS administration determines its success.
CRIS-Team WoS Importer:2022-07-15

Labour Induction with Misoprostol in German Obstetric Clinics: What Are the Facts on Such Use? - Kehl, Sven; Weiss, Christel; Rath, Werner; Schneider, Michael; Stumpfe, Florian; Faschingbauer, Florian; Beckmann, Matthias; Stelzl, Patrick (Geburtshilfe und Frauenheilkunde, 2021)
Subject While the synthetic prostaglandin E1 analogue misoprostol is the most effect labour induction agent, its use is off-label for the most part. For this reason, and in view of its potential adverse effects and varying approaches to its administration, the drug has recently once again become a focus of critical attention. The objective of this survey was thus to establish a record of labour induction with misoprostol in German clinics and determine the impact of the negative reporting on everyday obstetric practice.
CRIS-Team WoS Importer:2021-09-03

Lack of evidence for effects of lockdowns on stillbirth rates during the SARS-CoV-2 pandemic in Bavaria: analysis of the Bavarian perinatal survey from 2010 to 2020 - Stumpfe, Florian; Schneider, Michael; Antoniadis, Sophia; Mayr, Andreas; Fleckenstein, Tobias; Staerk, Christian; Kehl, Sven; Hermanek, Peter; Boehm, Julian; Scharl, Anton; Beckmann, Matthias; Hein, Alexander (Archives of Gynecology and Obstetrics, 2022)
Background: Internationally, potential effects of national SARS-CoV-2-related lockdowns on stillbirth rates have been reported, but data for Germany, including risk factors for fetal pregnancy outcome, are lacking. The aim of this study is to compare the stillbirth rates during the two first lockdown periods in 2020 with previous years from 2010 to 2019 in a large Bavarian cohort. Methods: This study is a secondary analysis of the Bavarian perinatal data from 2010 to 2020, including 349,245 births. Univariate and multivariable regression analyses were performed to investigate the effect of two Bavarian lockdowns on the stillbirth rate in 2020 compared to the corresponding periods from 2010 to 2019. Results: During the first lockdown, the stillbirth rate was significantly higher compared to the reference period (4.04 vs. 3.03 stillbirths per 1000 births; P = 0.03). After adjustment for seasonal and long-term trends, this effect can no longer be observed (P = 0.2). During the second lockdown, the stillbirth rate did not differ in univariate (3.46 vs. 2.93 stillbirths per 1000 births; P = 0.22) as well as in multivariable analyses (P = 0.68), compared to the years 2010 to 2019. Conclusion: After adjustment for known long-term effects, in this study we did not find evidence that the two Bavarian lockdowns had an effect on the rate of stillbirths.
CRIS-Team Scopus Importer:2022-11-25
Keywords: COVID-19; Stillbirths; Stillborn

Limited Effects of SARS-CoV-2 Pandemic-related Lockdowns and Reduced Population Mobility on Preterm Birth Rates: A Secondary Analysis of Bavarian Obstetric Quality Parameters from 2010 to 2020 - Stumpfe, Florian; Schneider, Michael Oliver; Hein, Alexander; Faschingbauer, Florian; Kehl, Sven; Hermanek, Peter; Boehm, Julian; Scharl, Anton; Beckmann, Matthias; Staerk, Christian; Mayr, Andreas (Geburtshilfe und Frauenheilkunde, 2022)
Introduction International studies on preterm birth rates during COVID-19 lockdowns report different results. This study examines preterm birth rates during lockdown periods and the impact of the mobility changes of the population in Bavaria, Germany. Material and Methods This is a secondary analysis of centrally collected data on preterm births in Bavaria from 2010 to 2020. Preterm births (< 37 weeks) in singleton and twin pregnancies during two lockdowns were compared with corresponding periods in 2010 - 2019. Fisher & apos;s exact test was used to compare raw prevalence between groups. Potential effects of two fixed lockdown periods and of variable changes in population mobility on preterm birth rates in 2020 were examined using additive logistic regression models, adjusting for long-term and seasonal trends. Results Unadjusted preterm birth rates in 2020 were significantly lower for singleton pregnancies during the two lockdown periods (Lockdown 1: 5.71% vs. 6.41%; OR 0.88; p < 0.001; Lockdown 2: 5.71% vs. 6.60%; OR = 0.86; p < 0.001). However, these effects could not be confirmed after adjusting for long-term trends (Lockdown 1: adj. OR = 0.99; p = 0.73; Lockdown 2: adj. OR = 0.96; p = 0.24). For twin pregnancies, differences during lockdown were less marked (Lockdown 1: 52.99% vs. 56.26%; OR = 0.88; p = 0.15; Lockdown 2: 58.06% vs. 58.91%; OR = 0.97; p = 0.70). Reduced population mobility had no significant impact on preterm birth rates in singleton pregnancies (p = 0.14) but did have an impact on twin pregnancies (p = 0.02). Conclusions Reduced preterm birth rates during both lockdown periods in 2020 were observed for singleton and twin pregnancies. However, these effects are reduced when adjusting for long-term and seasonal trends. Reduced population mobility was associated with lower preterm birth rates in twin pregnancies.
CRIS-Team WoS Importer:2022-07-29

Longitudinal Course of Short-Term Variation and Doppler Parameters in Early Onset Growth Restricted Fetuses - Baier, Friederike; Weinhold, Leonie; Stumpfe, Florian; Kehl, Sven; Pretscher, Jutta; Bayer, Christian M.; Topal, Nalan; Pontones, Constanza; Mayr, Andreas; Schild, Ralf Lothar; Schmid, Matthias; Beckmann, Matthias; et al. (Ultraschall in der Medizin, 2019)
PURPOSE: To evaluate the longitudinal pattern of fetal heart rate short term variation (STV) and Doppler indices and their correlation to each other in severe growth restricted (IUGR) fetuses. MATERIALS AND METHODS: In this retrospective study, pregnancies with a birth weight below the 10th percentile, born between 24 and 34 gestational weeks with serial Doppler measurements in combination with a computerized CTG (cCTG) with calculated STV were included. Longitudinal changes of both Doppler indices and STV values were evaluated with generalized additive models, adjusted for gestational age and the individual. For all measurements the frequency of abnormal values with regard to the time interval before delivery and Pearson correlations between Doppler indices and STV values were calculated. RESULTS: 41 fetuses with a total of 1413 observations were included. Over the course of the whole study period, regression analyses showed no significant change of STV values (p = 0.38). Only on the day of delivery, a prominent decrease was observed (mean STV d28-22: 7.97 vs. mean STV on day 0: 6.8). Doppler indices of UA and MCA showed a continuous, significant deterioration starting about three weeks prior to delivery (p = 0.007; UA and p < 0.001, MCA). Correlation between any Doppler index and STV values was poor. CONCLUSION: Fetal heart rate STV does not deteriorate continuously. Therefore, cCTG monitoring should be performed at least daily in these high-risk fetuses. Doppler indices of umbilical artery (UA) and middle cerebral artery (MCA), however, showed continuous deterioration starting about 3 weeks prior to delivery.
EVALuna2:212318

Predicting mammographic density with linear ultrasound transducers - Behrens, Annika; Fasching, Peter; Schwenke, Eva; Gaß, Paul; Häberle, Lothar; Heindl, Felix; Heusinger, Katharina; Lotz, Laura; Lubrich, Hannah; Preuß, Caroline; Schneider, Michael; Schulz-Wendtland, Rüdiger; et al. (European Journal of Medical Research, 2023)
Background: High mammographic density (MD) is a risk factor for the development of breast cancer (BC). Changes in MD are influenced by multiple factors such as age, BMI, number of full-term pregnancies and lactating periods. To learn more about MD, it is important to establish non-radiation-based, alternative examination methods to mammography such as ultrasound assessments. Methods: We analyzed data from 168 patients who underwent standard-of-care mammography and performed additional ultrasound assessment of the breast using a high-frequency (12 MHz) linear probe of the VOLUSON® 730 Expert system (GE Medical Systems Kretztechnik GmbH & Co OHG, Austria). Gray level bins were calculated from ultrasound images to characterize mammographic density. Percentage mammographic density (PMD) was predicted by gray level bins using various regression models. Results: Gray level bins and PMD correlated to a certain extent. Spearman’s ρ ranged from − 0.18 to 0.32. The random forest model turned out to be the most accurate prediction model (cross-validated R 2, 0.255). Overall, ultrasound images from the VOLUSON® 730 Expert device in this study showed limited predictive power for PMD when correlated with the corresponding mammograms. Conclusions: In our present work, no reliable prediction of PMD using ultrasound imaging could be observed. As previous studies showed a reasonable correlation, predictive power seems to be highly dependent on the device used. Identifying feasible non-radiation imaging methods of the breast and their predictive power remains an important topic and warrants further evaluation. Trial registration 325-19 B (Ethics Committee of the medical faculty at Friedrich Alexander University of Erlangen-Nuremberg, Erlangen, Germany).
CRIS-Team Scopus Importer:2023-10-13
Keywords: Breast cancer risk; Percent mammographic density; Ultrasound

Prevalence of SARS-CoV-2 in Pregnant Women Assessed by RT-PCR in Franconia, Germany: First Results of the SCENARIO Study (SARS-CoV-2 prEvalence in pregNAncy and at biRth In FrancOnia) - Hein, Alexander; Kehl, Sven; Häberle, Lothar; Tiemann, Carsten; Peuker, Rebecca; Mereutanu, Denise; Stumpfe, Florian; Faschingbauer, Florian; Meyer-Schlinkmann, Kirstin; Koch, Martin C.; Kainer, Franz; Dammer, Ulf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Detection of SARS-CoV-2-infected pregnant women admitted to maternity units during a pandemic is crucial. In addition to the fact that pregnancy is a risk factor for severe COVID-19 and that medical surveillance has to be adjusted in infected women and their offspring, knowledge about infection status can provide the opportunity to protect other patients and healthcare workers against virus transmission. The aim of this prospective observational study was to determine the prevalence of SARS-CoV-2 infection among pregnant women in the hospital setting. Material and Methods All eligible pregnant women admitted to the nine participating hospitals in Franconia, Germany, from 2 June 2020 to 24 January 2021 were included. COVID-19-related symptoms, secondary diseases and pregnancy abnormalities were documented. SARS-CoV-2 RNA was detected by RT-PCR from nasopharyngeal swabs. The prevalence of acute SARS-CoV-2 infection was estimated by correcting the positive rate using the Rogan-Gladen method. The risk of infection for healthcare workers during delivery was estimated using a risk calculator. Results Of 2414 recruited pregnant women, six were newly diagnosed RT-PCR positive for SARS-CoV-2, which yielded a prevalence of SARS-CoV-2 infection of 0.26% (95% CI, 0.10-0.57%). Combining active room ventilation and wearing FFP2 masks showed an estimated reduction of risk of infection for healthcare workers in the delivery room to < 1%. Conclusions The prevalence of newly diagnosed SARS-CoV-2 infection during pregnancy in this study is low. Nevertheless, a systematic screening in maternity units during pandemic situations is important to adjust hygienic and medical management. An adequate hygienic setting can minimise the calculated infection risk for medical healthcare workers during patients' labour.
CRIS-Team Scopus Importer:2022-02-25
Keywords: COVID-19; infection; pregnancy; prevalence; SARS-CoV-2

SARS-CoV-2 Infection in Pregnancy - a Review of the Current Literature and Possible Impact on Maternal and Neonatal Outcome - Stumpfe, Florian; Titzmann, Adriana; Schneider, Michael; Stelzl, Patrick; Kehl, Sven; Fasching, Peter; Beckmann, Matthias; Enßer, Armin (Geburtshilfe und Frauenheilkunde, 2020)
In December 2019, cases of pneumonia of unknown cause first started to appear in Wuhan in China; subsequently, a new coronavirus was soon identified as the cause of the illness, now known as Coronavirus Disease 2019 (COVID-19). Since then, infections have been confirmed worldwide in numerous countries, with the number of cases steadily rising. The aim of the present review is to provide an overview of the new severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2) and, in particular, to deduce from it potential risks and complications for pregnant patients. For this purpose, the available literature on cases of infection in pregnancy during the SARS epidemic of 2002/2003, the MERS (Middle East respiratory syndrome) epidemic ongoing since 2012, as well as recent publications on cases infected with SARS-CoV-2 in pregnancy are reviewed and reported. Based on the literature available at the moment, it can be assumed that the clinical course of COVID-19 disease may be complicated by pregnancy which could be associated with a higher mortality rate. It may also be assumed at the moment that transmission from mother to child in utero is unlikely. Breastfeeding is possible once infection has been excluded or the disease declared cured.
CRIS-Team Scopus Importer:2020-05-19
Keywords: 2019-nCoV; coronavirus; COVID-19; pregnancy; SARS-CoV-2

The Involvement of Cx43 in JNK1/2-Mediated Endothelial Mechanotransduction and Human Plaque Progression - Tauchi, Miyuki; Oshita, Kensuke; Urschel, Katharina; Furtmair, Roman; Kühn, Constanze; Stumpfe, Florian; Botos, Balazs; Achenbach, Stephan; Dietel, Barbara (International Journal of Molecular Sciences, 2023)
Atherosclerotic lesions preferentially develop at bifurcations, characterized by non-uniform shear stress (SS). The aim of this study was to investigate SS-induced endothelial activation, focusing on stress-regulated mitogen-activated protein kinases (MAPK) and downstream signaling, and its relation to gap junction proteins, Connexins (Cxs). Human umbilical vein endothelial cells were exposed to flow (“mechanical stimulation”) and stimulated with TNF-α (“inflammatory stimulation”). Phosphorylated levels of MAPKs (c-Jun N-terminal kinase (JNK1/2), extracellular signal-regulated kinase (ERK), and p38 kinase (p38K)) were quantified by flow cytometry, showing the activation of JNK1/2 and ERK. THP-1 cell adhesion under non-uniform SS was suppressed by the inhibition of JNK1/2, not of ERK. Immunofluorescence staining and quantitative real-time PCR demonstrated an induction of c-Jun and c-Fos and of Cx43 in endothelial cells by non-uniform SS, and the latter was abolished by JNK1/2 inhibition. Furthermore, plaque inflammation was analyzed in human carotid plaques (n = 40) using immunohistochemistry and quanti-gene RNA-assays, revealing elevated Cx43+ cell counts in vulnerable compared to stable plaques. Cx43+ cell burden in the plaque shoulder correlated with intraplaque neovascularization and lipid core size, while an inverse correlation was observed with fibrous cap thickness. Our results constitute the first report that JNK1/2 mediates Cx43 mechanoinduction in endothelial cells by atheroprone shear stress and that Cx43 is expressed in human carotid plaques. The correlation of Cx43+ cell counts with markers of plaque vulnerability implies its contribution to plaque progression.
CRIS-Team Scopus Importer:2023-02-03
Keywords: atherogenesis; endothelial dysfunction; gap junctions; MAPK; mechanotransduction; shear stress

The Shear Stress–Regulated Expression of Glypican-4 in Endothelial Dysfunction In Vitro and Its Clinical Significance in Atherosclerosis - Urschel, Katharina; Hug, Karsten; Zuo, Hanxiao; Büttner, Michael; Furtmair, Roman; Kühn, Constanze; Stumpfe, Florian; Botos, Balaz; Achenbach, Stephan; Yuan, Yan; Dietel-Schor, Barbara; Tauchi-Brück, Miyuki (International Journal of Molecular Sciences, 2023)
Retention of circulating lipoproteins by their interaction with extracellular matrix molecules has been suggested as an underlying mechanism for atherosclerosis. We investigated the role of glypican-4 (GPC4), a heparan sulfate (HS) proteoglycan, in the development of endothelial dysfunction and plaque progression; Expression of GPC4 and HS was investigated in human umbilical vein/artery endothelial cells (HUVECs/HUAECs) using flow cytometry, qPCR, and immunofluorescent staining. Leukocyte adhesion was determined in HUVECs in bifurcation chamber slides under dynamic flow. The association between the degree of inflammation and GPC4, HS, and syndecan-4 expressions was analyzed in human carotid plaques; GPC4 was expressed in HUVECs/HUAECs. In HUVECs, GPC4 protein expression was higher in laminar than in non-uniform shear stress regions after a 1-day or 10-day flow (p < 0.01 each). The HS expression was higher under laminar flow after a 1 day (p < 0.001). Monocytic THP-1 cell adhesion to HUVECs was facilitated by GPC4 knock-down (p < 0.001) without affecting adhesion molecule expression. GPC4 and HS expression was lower in more-inflamed than in less-inflamed plaque shoulders (p < 0.05, each), especially in vulnerable plaque sections; Reduced expression of GPC4 was associated with atherogenic conditions, suggesting the involvement of GPC4 in both early and advanced stages of atherosclerosis.
CRIS-Team Scopus Importer:2023-08-11
Keywords: atherosclerosis; endothelial dysfunction; glypican-4; heparan sulfate; plaque; sex differences; shear stress

The use of PAMG-1 testing in patients with preterm labor, intact membranes and a short sonographic cervix reduces the rate of unnecessary antenatal glucocorticoid administration - Kehl, Sven; Weiss, Christel; Pretscher, Jutta; Baier, Friederike; Faschingbauer, Florian; Beckmann, Matthias; Stumpfe, Florian (Journal of Perinatal Medicine, 2021)
Objectives: To assess the frequency of antenatal corticosteroid (ACS) administration in cases with shortened cervical length by addition of placental alpha-microglobulin-1 (PAMG-1) testing to sonographic examination. Methods: Single centre retrospective cohort study. Rate of ACS administration was compared between cases with cervical length between 15 and 25 mm and cases with positive PAMG-1 testing and cervical length between 15 and 25 mm. We evaluated the following outcome parameters: Rate of ACS administration, gestational age at delivery, time to delivery, delivery within seven days, delivery <34 and <37 weeks' gestation, rate of admission to neonatal intensive care unit (NICU). Results: In total, 130 cases were included. "PAMG-1 group" consisted of 68 women, 62 cases built the "historical control group". ACS administration was performed less frequently in the "PAMG-1 cohort" (18 (26%) vs. 46 (74%); p<0.001). The rate of delivery within seven days did not differ (2 (3%) vs. 4 (6.5%); p=0.4239). The rates of delivery <34 weeks' gestation (7 (10%) vs. 9 (15%); p=0.4643) and <37 weeks' gestation (19 (28%) vs. 26 (42%); p=0.0939) did not differ. Time to delivery interval was longer in the PAMG-1 group (61.5 vs. 43 days, p=0.0117). NICU admission occurred more often in the "historical control group" (22 (38%) vs. 28 (60%); p=0.0272). Conclusions: Addition of biomarker testing can help to avoid unnecessary ACS administrations in women with shortened cervical length.
CRIS-Team WoS Importer:2021-12-03